2014
DOI: 10.1155/2014/840170
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair Surgery: Outcome Evaluation by Using Noninvasive Cartilage Biomarkers Based on Quantitative MRI Techniques?

Abstract: Background. New quantitative magnetic resonance imaging (MRI) techniques are increasingly applied as outcome measures after cartilage repair. Objective. To review the current literature on the use of quantitative MRI biomarkers for evaluation of cartilage repair at the knee and ankle. Methods. Using PubMed literature research, studies on biochemical, quantitative MR imaging of cartilage repair were identified and reviewed. Results. Quantitative MR biomarkers detect early degeneration of articular cartilage, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 188 publications
(332 reference statements)
2
45
0
2
Order By: Relevance
“…22 However, studies have shown that some results cannot be explained by GAG measurements alone, but might be found in a combination of several quantitative MRI techniques, morphological, and clinical evaluation. 22,38 dGEMRIC is considered a valuable tool in evaluating cartilage quality, but there are also alternative MRI techniques available to assess cartilage quality, such as sodium MRI, T1 rho, and T2-mapping. 22 All limitations of dGEMRIC imaging considered in general and in this specific small size study, implementation of a strict contrast administration protocol, minimized patient motion during acquisition, postprocessing image registration, and minimal variation between observers should be sufficient to consider dGEMRIC indices as representative for cartilage quality with respect to GAG content/distribution in this study.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, studies have shown that some results cannot be explained by GAG measurements alone, but might be found in a combination of several quantitative MRI techniques, morphological, and clinical evaluation. 22,38 dGEMRIC is considered a valuable tool in evaluating cartilage quality, but there are also alternative MRI techniques available to assess cartilage quality, such as sodium MRI, T1 rho, and T2-mapping. 22 All limitations of dGEMRIC imaging considered in general and in this specific small size study, implementation of a strict contrast administration protocol, minimized patient motion during acquisition, postprocessing image registration, and minimal variation between observers should be sufficient to consider dGEMRIC indices as representative for cartilage quality with respect to GAG content/distribution in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most other cartilage scoring systems, in AMADEUS score the parameter defect size was included, since the choice of cartilage repair techniques may change for example from microfracturing, which is commonly used for small cartilage defects to osteochondral transplantation or autologous chondrocyte implantation. [19][20][21][22] For large defects, autologous chondrocyte implantation (ACI) is currently the cartilage repair technique of choice, although other techniques such as allografts or the Mega-OATS procedure exist. [23][24][25] Defect morphology/ depth was included, since first, indication for cartilage repair surgery may be made to a different time point if there is no full-thickness defect-but second, progression of defect morphology/ depth over time may be detected by implementation of this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Für eine suffiziente Beurteilung von Knorpelverletzungen sind häufig sowohl CT als auch MRT nötig, da die jewei-lige Größe der knöchernen und der knorpeligen Verletzungskomponente für die Therapieplanung und -entscheidung wichtig ist. Neben den herkömmlichen MRT-Sequenzen wurde versucht, durch spezielle Untersuchungsverfahren wie das T2 Mapping, das T1rho Mapping, das Delayed Gadolinium-enhanced MRI für Knorpel (dGEMRIC) und die diffusionsgewichtete Darstellung (Diffusion-weighted Imaging; DWI) eine bessere Abbildung des Knorpels zu erreichen [9]. Trotz des offensichtlichen Zuwachses an Darstellungsqualität fehlte leider oft der Zusammenhang mit den klinischen Ergebnissen im Langzeitverlauf [10].…”
Section: Bildgebende Diagnostikunclassified